Epidemiology, microbiology and mortality associated with community-acquired bacteremia in northeast Thailand: a multicenter surveillance study. - Manas Kanoksil; Anchalee Jatapai; Sharon J Peacock; Direk Limmathurotsakul (PLoS ONE)
Background National statistics in developing countries are likely to underestimate deaths due to bacterial infections. Here, we calculated mortality associated with community-acquired bacteremia (CAB) in a developing country using routinely available databases. Methods/principal findings Information was obtained from the microbiology and hospital database of 10 provincial hospitals in northeast Thailand, and compared with the national death registry from the Ministry of Interior, Thailand for the period between 2004 and 2010. CAB was defined in patients who had pathogenic organisms isolated from blood taken within 2 days of hospital admission without a prior inpatient episode in the preceding 30 days. A total of 15,251 CAB patients identified, of which 5,722 (37.5%) died within 30 days of admission. The incidence rate of CAB between 2004 and 2010 increased from 16.7 to 38.1 per 100,000 people per year, and the mortality rate associated with CAB increased from 6.9 to 13.7 per 100,000 people per year. In 2010, the mortality rate associated with CAB was lower than that from respiratory tract infection, but higher than HIV disease or tuberculosis. The most common causes of CAB were Escherichia coli (23.1%), Burkholderia pseudomallei (19.3%), and Staphylococcus aureus (8.2%). There was an increase in the proportion of Extended-Spectrum Beta-Lactamases (ESBL) producing E. coli and Klebsiella pneumoniae over time. Conclusions This study has demonstrated that national statistics on causes of death in developing countries could be improved by integrating information from readily available databases. CAB is neglected as an important cause of death, and specific prevention and intervention is urgently required to reduce its incidence and mortality.